Manipulation and measurement of pH sensitive metal–ligand binding using electrochemical proton generation and metal detection. Issue 9 (17th December 2015) - Read, Tania L.; Joseph, Maxim B.; Macpherson, Julie V.
Abstract : Boron doped diamond generator-detector electrodes can both change and monitor the binding state of the pH sensitive metal–ligand complex [Cu 2+ :TETA] by locally varying pH and measuring the free metal concentration. Abstract : Generator-detector electrodes can be used to both perturb and monitor pH dependant metal–ligand binding equilibria, in situ . In particular, protons generated at the generator locally influence the speciation of metal (Cu 2+ ) in the presence of ligand (triethylenetetraamine), with the detector employed to monitor, in real time, free metal (Cu 2+ ) concentrations.